The Effects of the Environment on the Drawings of an Extraordinarily Productive Orangutan (Pongo pygmaeus) Artist - Hanazuka, Yuki; Kurotori, Hidetoshi; Shimizu, Mika; Midorikawa, Akira (Frontiers in Psychology, 2019)
We report on the case of an extraordinary orangutan who spontaneously produced over a thousand drawings in 5 years. This female orangutan, Molly, started drawing when she was estimated to be 50 years old. Although it has been established that great apes spontaneously draw without training, she produced an enormous number of paintings in her old age, and the numbers of lines and colors in her drawings varied from day to day. As her drawings seemed to be affected by her surroundings, we attempted to analyze quantitatively relationships between her drawings and potentially influential factors during a specific period in which no ostensibly major events were observed. According to our results, her drawings were affected by the identity of her keeper, implying that her drawing behavior may have been affected by other environmental factors. Thus, drawings may serve as windows to the internal states of non-human primates.